Domain Wall Patterning and Giant Response Functions in Ferrimagnetic Spinels. Issue 23 (1st November 2021) - Kish, Lazar L.; Thaler, Alex; Lee, Minseong; Zakrzewski, Alexander V.; Reig‐i‐Plessis, Dalmau; Wolin, Brian A.; Wang, Xu; Littrell, Kenneth C.; Budakian, Raffi; Zhou, Haidong; Gai, Zheng; Frontzek, Matthias D.; et al.
Abstract: The manipulation of mesoscale domain wall phenomena has emerged as a powerful strategy for designing ferroelectric responses in functional devices, but its full potential is not yet realized in the field of magnetism. This work shows a direct connection between magnetic response functions in mechanically strained samples of Mn3 O4 and MnV2 O4 and stripe‐like patternings of the bulk magnetization which appear below known magnetostructural transitions. Building off previous magnetic force microscopy data, a small‐angle neutron scattering is used to show that these patterns represent distinctive magnetic phenomena which extend throughout the bulk of two separate materials, and further are controllable via applied magnetic field and mechanical stress. These results are unambiguously connected to the anomalously large magnetoelastic and magnetodielectric response functions reported for these materials, by performing susceptibility measurements on the same crystals and directly correlating local and macroscopic data. Abstract : Magnetostructural transitions in the ferrimagnetic spinels Mn3 O4 and MnV2 O4 are linked to increased spin–lattice coupling, from which novel magnetic domain structures emerge on the mesoscale. Small‐angle neutron scattering measures the response of these domain patterns to applied magnetic field and stress. Correlations between scattering and bulk probes demonstrate tuning of macroscopic response functions via alterations to the domain structure.